2021
DOI: 10.1136/bmjopen-2021-049916
|View full text |Cite
|
Sign up to set email alerts
|

Identifying women’s preferences for treatment of urinary tract infection: a discrete choice experiment

Abstract: ObjectiveTo identify the preferences of women regarding management of urinary tract infections (UTIs).DesignA discrete choice experiment of the preferences for certain treatment attributes was conducted by survey. Attributes included treatment duration, time to complaint resolution, complication risk, side effect risk and contribution to antimicrobial resistance.SettingGeneral population in the Netherlands, recruited via social media.ParticipantsWomen aged 18 years or older.Primary and secondary outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…In our study, women appreciated it if their GP made an effort to investigate possible causes and discuss different treatment options, including prophylactic strategies, for cystitis. These findings are similar to those of other qualitative studies that investigated optimizing antibiotic stewardship regarding UTIs and the need for SDM in the treatment of UTIs [ 29 – 31 ]. It is therefore indicated that it is useful to provide women with proper consultations, in which healthcare workers listen to women’s experiences and discuss different treatment options with them.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, women appreciated it if their GP made an effort to investigate possible causes and discuss different treatment options, including prophylactic strategies, for cystitis. These findings are similar to those of other qualitative studies that investigated optimizing antibiotic stewardship regarding UTIs and the need for SDM in the treatment of UTIs [ 29 – 31 ]. It is therefore indicated that it is useful to provide women with proper consultations, in which healthcare workers listen to women’s experiences and discuss different treatment options with them.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, findings from recent research have suggested that a considerable proportion of women are willing to tolerate less than optimal management in certain respects in order to avoid antimicrobial treatment for UTIs. These results indicate that there is a preference to avoid antimicrobial treatment and that resistance is strongest among women with a higher level of education, while younger women or those who had only experienced one previous UTI placed greater emphasis on quicker resolution of complaints [27].…”
Section: Discussionmentioning
confidence: 89%
“…The categories for UTI frequency were based on the Dutch College of Family Practitioners (NHG) guidelines and their definition for recurrent UTIs [3]. The categories for other characteristics were based on the scientific literature [10,33].…”
Section: Methodsmentioning
confidence: 99%